Unlocking practical wisdom through the inner voice of robots - Arianna Pipitone; Irene Seidita; John P. Sullins; Antonio Chella (Scientific Reports)
Abstract As Artificial Intelligence and Robotics evolve, the ethical implications of autonomous systems are becoming increasingly paramount. This article explores the role of a robot’s inner speech in enhancing human phronesis - the capacity for making ethical and contextually appropriate decisions. Phronesis is a complex human trait based on experience, personality, and values, and is crucial for decisions affecting others’ well-being. While artificial systems (i.e., robots) may not fully replicate human practical wisdom, they can support humans by stimulating reflection and helping in situations requiring careful consideration. This support can be more impactful if the robot has the ability for inner speech. The article examines whether a robot engaging in internal dialogue can help develop phronesis in people interacting with it, especially in contexts where caring of people with special needs is crucial. A group of participants was involved in a virtual game, where they had to care for a suffering person alongside a robot. Their decisions, in terms of task resolution and ethical considerations, allowed to assess if the robot’s inner speech increased participants’ awareness of the suffering person’s needs. Preliminary results are promising, highlighting the potential of thinking robots to assist in making ethical decisions.